Application of EASL 2017 criteria for switching hepatitis B patients from tenofovir disoproxil to entecavir or tenofovir alafenamide. Issue 10 (October 2020) - Roade, Luisa; Loglio, Alessandro; Borghi, Marta; Riveiro-Barciela, Mar; Soffredini, Roberta; Facchetti, Floriana; di Paolo, Dhanai; Tabernero, David; Lunghi, Giovanna; Esteban, Rafael; Buti, Maria; Lampertico, Pietro
Abstract: Background: To overcome safety limitations of tenofovir-disoproxil, EASL guidelines proposed switching chronic hepatitis B patients older than 60 years or with bone or renal disease to tenofovir-alafenamide or entecavir. Aims: To estimate the number of patients who would benefit from a treatment switch in a real-life setting. Methods: Consecutive hepatitis B patients receiving tenofovir-disoproxil before 31 December 2017 were enrolled in a cross-sectional study in two European hospitals. Clinical and virological data were recorded; renal function was assessed by estimated glomerular filtrate rate, serum phosphate and creatinine, proteinuria, and albuminuria; bone involvement by spine and femur DEXA scan. Results: In total, 565 patients included: 62 (18–91) years, 75% males, 92% Caucasian, 92% HBeAg-negative, 40% cirrhotic. Fifty-five percent of patients fulfilled age criterion (>60 years). Older patients had higher rates of cirrhosis (51% vs 26%, p <0.001), cardiovascular disease, and renal impairment. Thirty-six percent of patients met renal criteria, more commonly NA-experienced individuals (35% vs 21%, p =0.001); 17% had bone disease. Overall, 66% of patients had at least one criterion (71% if NA-experienced), 8% all three criteria, 28% age and renal criteria. Conclusions: Approximately two-thirds of patients receiving long-term tenofovir-disoproxil are candidates for an entecavir or tenofovir-alafenamide switch according to EASL recommendations